2018
DOI: 10.1177/0963689718794864
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cord Blood and Cord Blood-Derived Induced Pluripotent Stem Cells for Cartilage Regeneration

Abstract: Regeneration of articular cartilage is of great interest in cartilage tissue engineering since articular cartilage has a low regenerative capacity. Due to the difficulty in obtaining healthy cartilage for transplantation, there is a need to develop an alternative and effective regeneration therapy to treat degenerative or damaged joint diseases. Stem cells including various adult stem cells and pluripotent stem cells are now actively used in tissue engineering. Here, we provide an overview of the current statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…In our study, a relatively low chondrogenic induction could be related to the low percentage of KSR (5%) and shorter period of differentiation in 3D culture. The recent study of Nam’s group reprogrammed cord-blood derived cells in iPSC and 47 days (30 days in 3D culture) and 20% KSR presence in the medium were sufficient for the induction of well-formed cartilage-like spheres [24,51,52]. It is worth mentioning that in their approach the induction of MSC from PSC cells was performed via the 20% FBS supplementation of monolayer culture of EB outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a relatively low chondrogenic induction could be related to the low percentage of KSR (5%) and shorter period of differentiation in 3D culture. The recent study of Nam’s group reprogrammed cord-blood derived cells in iPSC and 47 days (30 days in 3D culture) and 20% KSR presence in the medium were sufficient for the induction of well-formed cartilage-like spheres [24,51,52]. It is worth mentioning that in their approach the induction of MSC from PSC cells was performed via the 20% FBS supplementation of monolayer culture of EB outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The simple yet complicated architecture of the articular cartilage compromises its natural capacity for self-repair [1]. The cartilage, with an avascular and alymphatic nature, is composed of dense layers of extracellular matrix (ECM) containing embedded distributed chondrocytes [2]. Cartilage lines the surface of the bone and provides a low-friction surface by absorbing external pressure or stimuli, which enables painless joint movement [3].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (30) indicated that the Wnt/β-catenin and TNF receptor superfamily of proteins were associated with the survival rate of UCBSCs, while inhibition of bone morphogenetic protein markers may prevent their independent differentiation. Several studies have produced feeder-free culture media, such as TeSRl that contains certain recombinant growth factors, which aim to enhance the ability of UCBSCs to regenerate (31,32). Zhou et al (33) demonstrated that the combination of activin inhibitors and MEK/ERK inhibitors increased the induction rate of UCBSCs.…”
Section: Differentiation Of Ucbscsmentioning
confidence: 99%